Plant watering system using mobile application - Zahid, M.S.M. (World Academy of Research in Science and Engineering, 2020)
Manual plant watering system bring many problems to plants especially for indoor plants. Lack of knowledge for the method of watering plants and measuring soil moisture are among the reasons plants fail to grow before they can be harvested. Improper attention to watering of plants and maintenance of soil moisture may expose the plants to some diseases. Home residential or agriculture institution sometimes miss their schedule of watering activity and soil moisture maintenance for several reasons. In this paper, a solution is provided to help them take care of their plants more efficiently. A mobile application is developed to automatically perform watering activity automatically based on soil moisture measurement. The application displays tank water level and soil moisture level in real-time. Wi-Fi communication technology is used so that users can monitor and perform watering activity even though they are mobile and quite far away from their plants. The system is also developed based on discussions and requirements given by a local farming and agriculture office.. Â© 2020, World Academy of Research in Science and Engineering. All rights reserved.